Mothers' reproductive and medical history misinformation practices as strategies against healthcare providers' domination and humiliation in maternal care decision-making interactions: an ethnographic study in Southern Ghana - Linda L. Yevoo; Irene A. Agyepong; Trudie Gerrits; Han van Dijk (BMC, 2018)
Abstract Background Pregnant women can misinform or withhold their reproductive and medical information from providers when they interact with them during care decision-making interactions, although, the information clients reveal or withhold while seeking care plays a critical role in the quality of care provided. This study explored 'how' and 'why' pregnant women in Ghana control their past obstetric and reproductive information as they interact with providers at their first antenatal visit, and how this influences providers' decision-making at the time and in subsequent care encounters. Methods This research was a case-study of two public hospitals in southern Ghana, using participant observation, conversations, interviews and focus group discussions with antenatal, delivery, and post-natal clients and providers over a 22-month period. The Ghana Health Service Ethical Review Committee gave ethical approval for the study (Ethical approval number: GHS-ERC: 03/01/12). Data analysis was conducted according to grounded theory. Results Many of the women in this study selectively controlled the reproductive, obstetric and social history information they shared with their provider at their first visit. They believed that telling a complete history might cause providers to verbally abuse them and they would be regarded in a negative light. Examples of the information controlled included concealing the actual number of children or self-induced abortions. The women adopted this behaviour as a resistance strategy to mitigate providers' disrespectful treatment through verbal abuses and questioning women's practices that contradicted providers' biomedical ideologies. Secondly, they utilised this strategy to evade public humiliation because of inadequate privacy in the hospitals. The withheld information affected quality of care decision-making and care provision processes and outcomes, since misinformed providers were unaware of particular women's risk profile. Conclusion Many mothers in this study withhold or misinform providers about their obstetric, reproductive and social information as a way to avoid receiving disrespectful maternal care and protect their privacy. Improving provider client relationship skills, empowering clients and providing adequate infrastructure to ensure privacy and confidentiality in hospitals, are critical to the provision of respectful maternal care.